Comparison of color stability and microleakage of bioactive material and a resin infiltration material on hypomineralization in primary teeth - Priyanka Purohit; Dinesh Rao; Sunil Panwar; Krittika Samaddar; Remi Ravi (Arbu Academic Publishing, 2023)
Aim: The current study aimed to evaluate and compare, in vitro the colour stability and microleakage of a bioactive material and a resin infiltration material on hypomineralization in primary teeth. Methods: Sixty human primary molars and incisors, which has been exfoliated or extracted were immersed in a demineralizing solution. 20 each specimen were treated by a bioactive compound (ACTIVA KIDS Bioactive-RESTORATIVE, PULPDENT, USA) (Group A), resin infiltration (Icon, DMG, Germany) (Group B) and as Control group (group C). Evaluation of colour stability and microleakage was done by using spectrophotometer analysis. The difference in color stability and microleakage of all three groups was determined by statistical analysis with a one-way ANOVA test for the proportion of the groups. p<0.05 was considered as statistically significant. Results: The bioactive compound showed statistically significant colour stability and lesser microleakage than resin infiltration material. Conclusions: Since bioactive compound exhibited better colour stability as well as showed lesser microleakage, it can be recommended for the restoration of the hypomineralized primary teeth.